The optimum nitrogen fertilizer rate for maize in the US Midwest is increasing - Mitchell E. Baum; John E. Sawyer; Emerson D. Nafziger; Michael J. Castellano; Marshall D. McDaniel; Mark A. Licht; Dermot J. Hayes; Matthew J. Helmers; Sotirios V. Archontoulis (Nature Communications)
Abstract Fertilizing maize at an optimum nitrogen rate is imperative to maximize productivity and sustainability. Using a combination of long-term (n = 379) and short-term (n = 176) experiments, we show that the economic optimum nitrogen rate for US maize production has increased by 2.7 kg N ha−1 yr−1 from 1991 to 2021 (1.2% per year) simultaneously with grain yields and nitrogen losses. By accounting for societal cost estimates for nitrogen losses, we estimate an environmental optimum rate, which has also increased over time but at a lower rate than the economic optimum nitrogen rate. Furthermore, we provide evidence that reducing rates from the economic to environmental optimum nitrogen rate could reduce US maize productivity by 6% while slightly reducing nitrogen losses. We call for enhanced assessments and predictability of the economic and environmental optimum nitrogen rate to meet rising maize production while avoiding unnecessary nitrogen losses.